Role Of Receiving Staff In Finance Department Operational Activities At Hotel Tentrem Semarang - Atsal Rais Adani; Emik Rahayu (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
In a hotel, it requires various needs in the form of operational goods, food ingredients, beverage ingredients or assets and this is where the role of the Receiving Officer is needed in the procedure for receiving goods. The process of receiving goods documents that require time for the approval of the General Manager makes it difficult for the Receiving Clerk to receive goods because when receiving goods the Receiving Clerk does not bring Purchase Orders and Purchase Requisitions because they are still in the process of approval and the Receiving Clerk's limited understanding of the quality of goods also hinders the procedure for receiving goods. this can be detrimental to the hotel. Guided by the Receiving Job Description, if the Purchase Order and Purchase Requisition documents are still in process, this will also hinder the Receiving Clerk in checking the quality and quantity of incoming goods. By using the interview method with 3 informants, which was given to several employees at the Ministry of Finance, so that the author is more accurate, it is also guided by the Literature Study studied. The author manages these sources of information into a result of field facts, so that the writer can provide conclusions on the problems that arise and provide advice to management. The data collection method used in this study is a qualitative method with a descriptive type. Data collection techniques using observation techniques, interviews, and documentation, in order to obtain accurate data and documents. The people interviewed were Receiving Officer,Cost Control, Buyer, Purchasing Officer